Respuesta :

aksnkj

Therefore, the expression equivalent to the given expression [tex]\sqrt x+11=15[/tex] is [tex]x=16[/tex].

The given expression is,

[tex]\sqrt x+11=15[/tex]

It is required to solve the given expression.

How to solve the expression?

Firstly, solve for the constant terms and then take square of both sides of the equation.

The given equation can be solved as,

[tex]\sqrt x+11=15\\ \sqrt x=4\\ x=4^2\\ x=16[/tex]

Therefore, the expression equivalent to the given expression [tex]\sqrt x+11=15[/tex] is [tex]x=16[/tex].

For more details about expression, refer to the link;

https://brainly.com/question/13947055

The equation is equivalent to the given equation is [tex]\sqrt{x} =15-11[/tex].

Given that

Equation; [tex]\rm \sqrt{x} +11 =15[/tex]

We have to determine

Which equation is equivalent to the given equation?

According to the question

To determine the equation is equivalent to the given equation following all the steps given below.

Equation; [tex]\rm \sqrt{x} +11 =15[/tex]

Then,

Subtracting 11 from both sides.

[tex]\rm \sqrt{x} +11 =15\\\\\rm \sqrt{x} +11-11 =15-11\\\\\rm \sqrt{x} =15-11[/tex]

Hence, the equation is equivalent to the given equation is [tex]\sqrt{x} =15-11[/tex].

To know more about Equation click the link given below.

https://brainly.com/question/15622027

Ver imagen psm22415
ACCESS MORE